2018
DOI: 10.31219/osf.io/rdjkv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strategi Pengembangan Model Pembelajaran Transformatif

Abstract: AbstrakPembelajaran transformatif adalah proses pembelajaran yang 'mendekatkan' para peserta didik kepada kenyataan, menghadirkan pengetahuan yang kritis-reflektif, dengan memposisikan guru lebih sebagai fasilitator untuk mengarahkan dan mendorong proses tersebut. Dalam tulisan ini akan diulas pemaknaan dan lingkup pembelajaran transformatif yang sesuai dengan perkembangan diskusi kontemporer. Sehubungan dengan hal itu pula, beberapa pendekatan, strategi, dan metode yang relevan juga disajikan untuk menjadi pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…Interest To Learn Susanto (2013) also stated that students' interest in certain subjects cannot be separated from the influence of the learning system organized by teachers at school. The indicator of interest in learning according to (Lestari & Yudhanegara, 2018) is students' feelings of enjoyment in the learning process which is different from before, interest in learning appears when students make project plans and scheduling, show attention when learning, and involvement in learning arises from the steps beginning to end, which is in accordance with the opinion of Priansa (2017) who states that Project-Based Learning (PjBL) is an effort to change teachercentered learning into student-centered learning. In this research, what will be observed is how much interest students have in learning towards Project-Based Learning (PjBL).…”
Section: Interest To Learnmentioning
confidence: 59%
“…Interest To Learn Susanto (2013) also stated that students' interest in certain subjects cannot be separated from the influence of the learning system organized by teachers at school. The indicator of interest in learning according to (Lestari & Yudhanegara, 2018) is students' feelings of enjoyment in the learning process which is different from before, interest in learning appears when students make project plans and scheduling, show attention when learning, and involvement in learning arises from the steps beginning to end, which is in accordance with the opinion of Priansa (2017) who states that Project-Based Learning (PjBL) is an effort to change teachercentered learning into student-centered learning. In this research, what will be observed is how much interest students have in learning towards Project-Based Learning (PjBL).…”
Section: Interest To Learnmentioning
confidence: 59%
“…Selain itu juga berdampak pada kemampuan siswa dalam membangun hubungan antara konsep, materi dengan kehidupan nyata sehingga membuat siswa kurang termotivasi dan merasakan pentingnya belajar untuk masa depan (Chasanah et al, 2020). Banyak kegagalan matematika di sekolah dan madrasah karena disebabkan penggunaan metode dan pendekatan tradisional yang tidak cocok dengan cara kebanyakan siswa belajar (Kurniasih & Berlin, 2017).…”
Section: Matematikaunclassified
“…Hasil belajar merupakan suatu pencapaian siswa karena usaha serta kemampuan penguasaan pengetahuan yang diperoleh setelah kegiatan belajar (Priansa, 2017). Adapun hasil belajar dipengaruhi oleh beberapa faktor seperti faktor internal dan eksternal (misalnya peran orang tua dan motivasi belajar).…”
Section: Pendahuluanunclassified